124 Heterogeneity of Allergen Epitope-specific CD4+ T Cells Responses: Steps Toward Optimal Composition for Peptide-based Immunotherapy - Wambre, Erik (World Allergy Organization Journal, 2012)
BACKGROUND: Peptide-based allergen immunotherapy is a promising alternative to conventional allergy vaccine. However, the optimal composition of such vaccines, in terms of the choice of the appropriate peptides, has remained unclear. Knowledge of the epitope-specific T cell responses to allergens can give important information on the pathogenesis and regulation of allergic inflammation. In this study we sought to identify candidate allergen-epitopes that can be used to improve peptide-based allergen immunotherapy. METHODS: Tetramer Guided Epitope Mapping was first used to identify CD4+ T cell epitopes for group 1 and group 5 timothy grass pollen allergens. MHC class II tetramer technology was then used in an ex vivo approach to assess the grass pollen-specific CD4(+) T cell responses in allergic and non-allergic individuals. The frequency, surface marker phenotype and cytokine profile of these cells were directly analysed by flow cytometry. RESULTS: CD4+ T cell responses to Timothy grass allergens are directed to a broad range of epitopes characterized by defined immunodominance hierarchy patterns. We observed heterogeneity of phenotype within the allergen-specific CD4+ T cells that depends on the epitope for which the cells are specific. T cell epitopes associated with production of IL-10 or IFN-g are recognized at low frequencies in both allergic and healthy individuals. In contrast, allergy-associated epitopes are only recognized in allergic individuals by high frequency, terminally differentiated allergen-specific CD4+ T cells, which are susceptible to deletion by repeated stimulation with high doses of antigen. Allergen-specific immunotherapy caused significant changes in the epitopes hierarchy of the grass pollen allergen-specific memory CD4 T cell pool. CONCLUSIONS: The ability to evaluate epitope-specific T cell responses to allergens can give important information on the pathogenesis and regulation of allergic inflammation and could be of great use in designing peptide-based allergy vaccination strategies. Some epitopes may play a prominent role in driving a protective response, while others may directly impair the pathogenic response.